PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA OMAR BARBERSHOP DI PEKANBARU - Fhajaridaus Muhamad; Alwie Furwanti Alvi; Mahardi Mahardi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of service quality and price on customer satisfaction and customer loyalty at Omar Barbershop in Pekanbaru. The population in this research were 100 respondents with certain criteria. Data analysis used path analysis through SPSS 26.00. The results of this study indicate that Service Quality and Price have a positive and significant impact on Customer Satisfaction. Service Quality and Price have a positive and significant influence on Customer Loyalty. Customer Satisfaction has a positive and significant influence on Customer Loyalty. Service Quality and Price have a positive and significant influence on Customer Loyalty with Customer Satisfaction as a mediating variable. Researchers suggest companies to continue to improve Service Quality to increase Customer Satisfaction and Loyalty.Keywords: Service Quality, Price, Customer Satisfaction, Customer Loyalty